Capital investments for the future of Serbia: Road transport infrastructure and "Expo 2027" - Aleksić Snežana B. (Megatrend Revija, 2024)
The Government of the Republic of Serbia announced the upcoming World Expo "Expo 2027" as a development opportunity for Belgrade and Serbia. Although for the needs of holding this exhibition, a location in the youngest Belgrade municipality, Surčin, has been determined, nevertheless, this large infrastructural project is not only closely related to the location where the exhibition will be held, but it is predicted that its economic benefits will be reflected to a greater or lesser extent on all regions of the Republic of Serbia. First of all, this assumption refers to the segment of modernization and construction of Serbian traffic infrastructure, with a special emphasis on road traffic. By building modern high-speed roads and highways, which are integrated into the already existing network of Serbian, but also important European and global land corridors, the Republic of Serbia, thanks to its geostrategic position, without a doubt positions itself as a key factor within the network of global roads that they connect East with West, North with south. Capital investments: investment in road transport infrastructure and works on the construction of the complex where Expo 2027 will be held, as part of the economic development strategy of the Republic of Serbia, entail other key factors of social change, which, in addition to socio-economic improvement, can contribute and suppressing the negative trend of demographic decline, and in a broader, geopolitical sense, can bring the Republic of Serbia a better positioning on the international geoeconomic and geopolitical plane.